Dispositional mindfulness and employment status as predictors of resilience in third year nursing students: a quantitative study. Issue 4 (2nd June 2016) - Chamberlain, Diane; Williams, Allison; Stanley, David; Mellor, Peter; Cross, Wendy; Siegloff, Lesley
Abstract: Background: Nursing students will graduate into stressful workplace environments and resilience is an essential acquired ability for surviving the workplace. Few studies have explored the relationship between resilience and the degree of innate dispositional mindfulness, compassion, compassion fatigue and burnout in nursing students, including those who find themselves in the position of needing to work in addition to their academic responsibilities. Aim: This paper investigates the predictors of resilience, including dispositional mindfulness and employment status of third year nursing students from three Australian universities. Design: Participants were 240 undergraduate, third year, nursing students. Participants completed a resilience measure (Connor–Davidson Resilience Scale, CD‐RISC), measures of dispositional mindfulness (Cognitive and Affective Mindfulness Scale Revised, CAMS‐R) and professional quality of life (The Professional Quality of Life Scale version 5, PROQOL5), such as compassion satisfaction, compassion fatigue and burnout. Method: An observational quantitative successive independent samples survey design was employed. A stepwise linear regression was used to evaluate the extent to which predictive variables were related each to resilience. Results: The predictive model explained 57% of the variance in resilience. Dispositional mindfulness subset acceptance made the strongest contribution, followed by the expectation of a graduate nurse transition programme acceptance, with dispositional mindfulness total score and employment greater than 20 hours per week making the smallest contribution. This was a resilient group of nursing students who rated high with dispositional mindfulness and exhibited hopeful and positive aspirations for obtaining a position in a competitive graduate nurse transition programme after graduation.